Reversed halo sign in acute pulmonary embolism and infarction. (June 2013) - Casullo, Joseph; Semionov, Alexandre
Background: The reversed halo sign, originally described in cryptogenic organizing pneumonia, has been observed in a variety of pulmonary diseases, including pulmonary embolism (PE). Purpose: To describe the computed tomographic (CT) findings in patients with the reversed halo sign and acute PE at initial presentation and in subsequent scans. Material and Methods: Contrast-enhanced CT examinations of 12 patients with the reversed halo sign and acute PE were analyzed retrospectively. The diagnosis of pulmonary embolism was made by CT angiography in 11 cases and by a routine contrast-enhanced scan of the chest in the other case. Follow-up scans of seven patients and follow-up radiographs of two patients were also examined retrospectively. The average age of the patients was 49 years (range, 21–80 years). Seven (58%) patients were women. Six patients had no significant medical history, and six patients had deep venous thrombosis initially. Results: The reversed halo sign was observed as a single lesion in 10 patients; in two patients, two lesions were found. The lesions, all pleural-based, occurred more frequently in the lower lobes and were associated with acute thromboemboli in segmental and subsegmental pulmonary arteries of the corresponding segment. Ten (10/14, 71%) lesions displayed an ellipsoid configuration, two (2/14, 14%) had a pyramidal shape, and two involved an almost entire pulmonary segment. The average largest dimension was 3.9 cm (range, 2.1–6.7 cm). All lesions subtended one or more bronchovascular bundles; three (3/14, 21%) showed air-bronchograms, and a thromboembolus was identified in the subtended arteries in nine (9/14, 64%) lesions. In succeeding CT scans (eight lesions) and follow-up radiographs (three lesions), the lesions became smaller, and the majority evolved into pleural-based linear scars by 7 months. Conclusion: The reversed halo sign very likely corresponds to pulmonary infarction in patients with acute PE. Its recognition may have important clinical implications.